Development of the fracture-based flexibility index for asphalt concrete cracking potential using modified semi-circle bending test parameters. (15th July 2016) - Ozer, Hasan; Al-Qadi, Imad L.; Lambros, John; El-Khatib, Ahmad; Singhvi, Punit; Doll, Berangere
Highlights: A fracture test method was developed to evaluate fracture resistance of asphalt mixes. The method is able to discriminate performance of asphalt mixes with varying recycled content. Flexibility index is good agreement with field fatigue failure of asphalt mixes. Abstract: Asphalt concrete (AC) pavement sustainability can be achieved by enhancing mixture durability, improving construction practices, optimizing pavement design, and maximizing the use of recycled resources to reduce life-cycle investments. Recycled materials are commonly used to improve sustainability of AC pavement as they replace natural resources and reduce initial construction costs and greenhouse gases during the material production phase. However, net savings, in terms of environmental and economic impact, can only be realized if the performance targeted by the initial design is achieved. The use of RAP and RAS may result in a significant reduction in the demand for virgin, quarried aggregates and, more importantly, asphalt binder. However, replacing virgin materials in AC mixtures with aged, stiffer binders poses numerous technical challenges in terms of mixture volumetrics and thermal (low temperature) and flexural fatigue cracking resistance. This paper introduces a practical fracture test method to screen AC mixtures' cracking resistance using the semi-circular bending test geometry. The selection procedure of the test method is presented along with the development of a flexibility index (FI) derived from the load-displacement curves. A discussion about the effect of viscoelasticity on fracture process is provided. The results indicate positive correlation between SCB test results and other independent fatigue tests. The proposed FI reflects positive correlation with the crack velocity, indicating brittleness of the materials, obtained from the same SCB experiments. The paper also provides a validation of the proposed IL-SCB test method results, including fracture energy and flexibility index (FI), using the number of cycles to fatigue cracking failure obtained from an accelerated pavement test sections.